Pharmacokinetics and tissue distribution of pefloxacin mesylate in chickens. (26th December 2017) - Lin, Shuqian; Li, Guiming; Zhao, Zengcheng; Fu, Jian; Feng, Minyan; Song, Minxun; Huang, Zhongli; Yang, Shifa; Wang, Shuli; Wan, Renzhong
Abstract: A specific, sensitive and stable high‐performance liquid chromatography (HPLC)‐based analytical method was established to determine the level of pefloxacin mesylate (PM) in the plasma and various tissues of chickens. Chickens were randomly assigned to 12 equal experiment groups, including 11 treatment groups and one control group. The chickens in the treatment groups received oral administration of PM and were sacrificed at different pre‐determined time points, with their blood and various organs harvested, extracted and analyzed by HPLC to quantify the level of the residual antibiotic. Method validation studies indicated that the HPLC measurement showed excellent precision, reproducibility, stability and robustness. The obtained pharmacokinetic parameters suggested that PM reached peak levels in various tissues within 1–2 h after its oral administration, and was mainly concentrated in liver and kidney. The antibiotic was also found to be cleared from chicken crureus, brain, testes, ovaries and pancreas at higher rates compared with other organs. Overall, the rapid accumulation of PM could at least be partially attributed to its relatively slow organ clearance. These results could serve as a useful guidance for the rational use of PM and other quinolone‐derived antimicrobials in the treatment of infectious diseases in chickens and other animals.